Three-dimensional Measurement of Specular Surfaces Based on the Light Field - Panyu Zhou (IEEE Photonics Journal, 2020)
As an important branch of computational optics, the light field can simultaneously record the spatial intensity and propagation direction of light, which provides a new way to realize three-dimensional (3D) measurement. Although light field measuring system (LFMS) can quickly detect nontransparent surfaces, specular light affects the overall measurement result. In this paper, an LFMS based on a diffuse light source and polarization technology is proposed to eliminate specular light and obtain a more accurate 3D reconstruction result in one exposure. During the measurement, a series of images corresponding to continuously varying polarization angle are captured, in which the value(V)-channel value distribution is used as the criterion of specular light removal efficiency, and hence, the image at the optimal polarization angle is obtained, in which the influence of specular light is removed. The depth map and specular light removal efficiency are experimentally compared with those of the traditional LFMS. The experimental results show that the depth map error can be greatly reduced, which further verifies the feasibility of the proposed method and system. The present study can be extended to the traditional optical system or other machine vision measurement methods involving specular light.